2019
DOI: 10.1103/physrevlett.122.036801
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal Phase Diagram of the Superfluid Density in LaAlO3/SrTiO3 Revealed by an Interfacial Waveguide Resonator

Abstract: We explore the superconducting phase diagram of the two-dimensional electron system at the LaAlO 3 /SrTiO 3 interface by monitoring the frequencies of the cavity modes of a coplanar waveguide resonator fabricated in the interface itself. We determine the phase diagram of the superconducting transition as a function of the temperature and electrostatic gating, finding that both the superfluid density and the transition temperature follow a dome shape but that the two are not monotonically related. The ground st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 52 publications
(60 reference statements)
2
16
2
Order By: Relevance
“…More recently, magnetotransport data on LAO/STO using different substrate crystalline orientations reveal a robustness of superconductivity for the heavy-mass electrons from d xz and d yz orbitals [41], while the light-mass electrons from d xy have higher mobility and thus dominate the normal state charge transport behavior instead. In addition, several microwave resonator measurements [42,43] also revealed that the superfluid density at LAO/STO interface is more than an order of magnitude lower than the electron density. Those results are in accord with our observation of the unusual weak R dependence on the Pauli-paramagnetic coupling strength in sample A as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, magnetotransport data on LAO/STO using different substrate crystalline orientations reveal a robustness of superconductivity for the heavy-mass electrons from d xz and d yz orbitals [41], while the light-mass electrons from d xy have higher mobility and thus dominate the normal state charge transport behavior instead. In addition, several microwave resonator measurements [42,43] also revealed that the superfluid density at LAO/STO interface is more than an order of magnitude lower than the electron density. Those results are in accord with our observation of the unusual weak R dependence on the Pauli-paramagnetic coupling strength in sample A as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are also definite indications of intrinsic inhomogeneities in the normal 24,25 and superconducting [26][27][28] states of the LAO/STO interface originating either from structural domains or electronic phase separation 29 . Therefore, the superconducting phase is likely to be marked by nonuniform superconducting islands 28,30,31 . While these strong nonmagnetic inhomogeneities, at first sight, can be incompatible with an unconventional type of pairing, it has been recently figured out that extra internal degrees of freedom such as orbitals, sublattices, or valleys can protect Cooper pairs from strong scattering 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there are also definite indications of intrinsic inhomogeneities in the normal [24,25] and superconducting [26][27][28] states of the LAO/STO interface originating either from structural domains or electronic phase separation [29]. Therefore, the superconducting phase is likely to be marked by nonuniform superconducting islands [28,30,31]. While these strong nonmagnetic inhomogeneities at first sight can be incompatible with an unconventional type of pairing, it has been recently figured out that extra internal degrees of freedom such as orbitals, sublattices, or valleys can protect Cooper pairs from strong scattering [32].…”
mentioning
confidence: 99%